2023
DOI: 10.7150/jca.85032
|View full text |Cite
|
Sign up to set email alerts
|

Cdc42 Regulates the Expression of Cytoskeleton and Microtubule Network Proteins to Promote Invasion and Metastasis of Progeny Cells Derived from CoCl2-induced Polyploid Giant Cancer Cells

Abstract: Purpose: Our previous studies have shown that CoCl 2 can induce the formation of polyploid giant cancer cells (PGCCs) and PGCCs could produce progeny cells via asymmetric division. In this study, the molecular mechanism by which PGCCs generate progeny cells with high invasion and migration abilities was explored. Methods: In this study, PGCCs induced by CoCl 2 produced progeny cells via asymmetric division, which was observed dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Although most of PGCCs succumb to cell death, some can survive and acquire cancer stem cells properties [ 19 , 23 ]. PGCCs are also considered to be a key factor in the process of tumorigenesis, metastasis and therapy resistance [ 24 , 25 ]. It seems necessary to pay more attention to PGCCs, a cancer cell subpopulation, in different aspects of tumor biology and therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Although most of PGCCs succumb to cell death, some can survive and acquire cancer stem cells properties [ 19 , 23 ]. PGCCs are also considered to be a key factor in the process of tumorigenesis, metastasis and therapy resistance [ 24 , 25 ]. It seems necessary to pay more attention to PGCCs, a cancer cell subpopulation, in different aspects of tumor biology and therapy.…”
Section: Discussionmentioning
confidence: 99%
“…121 Several studies have reported cell cycle arrest in PGCCs. [122][123][124][125][126] In current reports, terminologies related to cell cycle arrest of PGCCs include G2 cell cycle arrest, G Alert /spG0/G0 cells, arrested in the G0/G1 phase, quiescence, slow-cycling states, dormant state and proliferative arrest. Alhaddad L et al discussed the radioresistance related to the proportion of dormant PGCCs by the Ki-67/EdU staining features enriching in three subpopulations (G Alert , spG0, G0).…”
Section: Pgccs Have the Properties Of Dormant Cancer Cellsmentioning
confidence: 99%
“…Cdc42 overexpression takes a part in the invasion and migration of PGCCs and daughter cells. 123 In summary, PGCCs maintain cell cycle arrest and exhibit high migration and invasion rates when dormant.…”
Section: Pgccs Have the Properties Of Dormant Cancer Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Zheng et al found that after CoCl 2 treatment, the expression of Cdc42 and PAK1 increased, promoting the nuclear expression of phosphorylated stathmin (STMN1). This process enhances the proliferation, invasion, and migration of PGCCs and their daughter cells through cytoskeletal remodeling ( Zheng et al, 2023 ). Targeting PGCCs and their progeny can thus be a strategic direction.…”
Section: Therapies Targeting Pgccsmentioning
confidence: 99%